Training on Police Investigating Officers in Medico-Legal Formalities in Deceased Organ Donation – Our Experience from Tamil Nadu in India. (August 2017) - Kanvinde, Hemal; Shroff, Sunil; Raghuram, Lalitha; Velankanni, Sunitha; Navin, Sumana
Abstract : Introduction: In the year 1995 India accepted brain death as form of death for organ donation by passing a legislation in the parliament. The transplant registry of Tamil Nadu state indicates majority (77%) of brain death are due to road traffic accidents and hence these requires medico-legal clearance from the Police before they can be accepted for organ donation. The role of police in such cases decides if they provide permission for organ donation or not. The police investigating officer play a vital role for conducting the inquest, validating the family consent, and proceeding with post-mortem after donation. The certification process has two sets of Apnoea tests 6 hours apart. Brain death and legal procedures are not part of the formal police training curriculum. The investigating officer does not have an idea of brain death and organ donation. During a donation case, the transplant coordinators well as the ICU doctors are expected to explain the process to the officer when they come for the inquest. This can cause undue a delay in the donation process and lifesaving organs can be lost due to the delays. Method: MOHAN Foundation began a series of consultations with senior police officials and started training programs for police school instructors, inspectors, sub inspectors and constables in the southern state of Tamil Nadu. Presentations, cases studies, resource book, posters, meeting with recipients and test module were some of the tools developed and used in the training. In the past 5 years 4000 police personnel were trained on their Role in Deceased Organ Donation. Results: Sensitization helped in decreasing the delays in providing consent to proceed with organ donation. Establishing of 'Green corridors' (when traffic comes to halt) on the roads to move organs through in the city. The most important impact was the establishment of a "Nodal Officer" for Organ Donation from the Law and Order Division to ease the 'pain points' with the police. Conclusion: Training on Police Investigating Officers resulted in better understanding by the police of the required legal procedures & brain death and the value of the time between the apnoea tests. The Police have come forward with novel methods to ease of the process of organ donation. This training module is now being replicated in other Indian states.